Studying the Relationship between the Self-Sufficiency Activities of Imam Khomeini Relief Committee and the Empowerment of Women Heads of Households in Qahavand Region - Sarai, Behrouz; Yaghoubi Farani, Ahmad (International Journal of Business Management and Entrepreneurship, 2025)
One of the important issues for women heads of households is their empowerment. The overall objective of this study was to study the relationship between the self-sufficiency activities of Imam Khomeini Relief Committee and the empowerment of women heads of households in Qahavand region. The statistical population of this study included all women heads of households in Qahavand in 2019-2022 who benefited from the self-sufficiency activities of the Relief Committee, which numbered 627 people. Of these, 238 people were selected as the available sample based on the Cochran formula. The main tool in this study was the Empowerment of Women Heads of Households Questionnaire. In total, the results of the one-sample parametric t-test were examined in three dimensions of social empowerment (mean: 3.83), economic (mean: 3.81), and psychological (mean: 3.73). The results showed that the self-sufficiency activities of the Relief Committee had the greatest impact on social empowerment. This means that the self-sufficiency activities of the Imam Khomeini Relief Committee (RA) based on education, acquisition of job skills and techniques, strengthening self-confidence and creating motivation, have brought them into the larger social environment.